Four Flu Pandemics: Lessons that Need to Be Learned. Issue 4 (December 2021) - Pineo, Ronn
This article explores the history of influenza, focusing on the four major flu pandemics in the last century and a half, outbreaks starting in 1889, 1918, 1957, and 1968. The article looks closely at flu etiology and the historical puzzles over which flu subtype was responsible for each major outbreak. Some mysteries regarding pandemic influenza remain, with core questions stubbornly refusing to yield answers. This article seeks to explore the history of flu in the hope that we can take away some lessons learned as we try to get ready for potential future flu pandemics.